Ensaio em dois tempos: revivendo Antígona, a prisioneira (ouvirOUver, 2018)
Este ensaio, em um primeiro momento, apresenta uma reflexão sobre um processo artístico envolvendo a personagem de Antígona, da primorosa peça de Sófocles [400 a.C] e, em seguida, montagens de textos e fotografias. Intenta trabalhar o tempo como elemento da narrativa e da montagem literária e visual. ABSTRACTA two-round essay: reviving Antigone, the prisoner.This essay, at a first moment, presents a reflection about an artistic process involving the character of Antigone, taken from Sophocles's exquisite play [400 a.C] and, following that, an assemblage of texts and photographs. The theatricality of photographic images, the literary narrative, and the assemblage were the procedures sought in this work. It aims to deal with "time" as an element for the narrative and the visual and literary assemblage.Key-words: photography, literature, story , Antigone.